Succeeding on your own (Wheeling, IL : Film Ideas, 2007)
Money management is a essential life skill for success in adulthood. Student debt along with housing, clothing, food, insurance, automobile, savings and entertainment combine to put a serious strain on an income. Discusses the challenges of living within a budget and income.
Includes index.
Keywords: Finance, Personal